2001
DOI: 10.1152/ajpendo.2001.280.4.e608
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine increases intracellular Ca2+in the rat pituitary folliculostellate cells in primary culture

Abstract: Pituitary folliculostellate cells (FSCs) are thought to partially inhibit pituitary hormone secretion through a paracrine mechanism. In this process, one of the important questions is what factors regulate the function of FSCs. Because ACh is synthesized in and possibly released from the corticotrophs and lactotrophs, we examined whether FSCs respond to ACh by the method of Ca2+ imaging in primary cultured FSCs from male Wistar rats. ACh (30 nM-3 microM) increased intracellular calcium concentration ([Ca2+](i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…It causes a dose-dependent release of Anx A1 from TtT/GF cells. Acetylcholine acts on cultured primary rat F-S cells via muscarinic receptors to stimulate calcium transients by causing release from intracellular stores [28]. However, our TtT/GF cell cultures fail to generate calcium transients to even larger doses of acetylcholine, although they readily respond in this way to ATP (Morris, Williams, Christian, unpublished observations).…”
Section: Inputs To F-s Cells: Receptors and Mecha-nisms Of Actionmentioning
confidence: 89%
See 2 more Smart Citations
“…It causes a dose-dependent release of Anx A1 from TtT/GF cells. Acetylcholine acts on cultured primary rat F-S cells via muscarinic receptors to stimulate calcium transients by causing release from intracellular stores [28]. However, our TtT/GF cell cultures fail to generate calcium transients to even larger doses of acetylcholine, although they readily respond in this way to ATP (Morris, Williams, Christian, unpublished observations).…”
Section: Inputs To F-s Cells: Receptors and Mecha-nisms Of Actionmentioning
confidence: 89%
“…While the availability of these cell lines has been most useful, there is often the implicit assumption that these cell lines entirely represent the native F-S cells. However, TtT/GF cells lack nNOS [27] and we have recently found that, unlike native rat cultured F-S cells [28], TtT/GF cells do not respond to acetylcholine by a rise in intracellular calcium ([Ca] i ) although they can respond to acetylcholine by exporting Anx A1 [29]. The first human F-S cell line (PDFS) was derived spontaneously from a clinically non-functioning pituitary macroadenoma [30].…”
Section: F-s Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbachol inhibition of GH release in aggregates can be blocked by the calcium channel blockers cadmium and verapamil (594), consistent with the activation of nNOS by intracellular free calcium (3, 598). FS cells express muscarinic receptors, probably of the M1 type, that mediate activation of phospholipase C and intracellular free Ca 2+ rises (4, 599). Carbachol does not inhibit GH secretion in the GH3 cell line cultured as aggregates (5, 594).…”
Section: Corticotrophs As Autocrine/paracrine Cells and Targetsmentioning
confidence: 99%
“…FS cells express β1 and β2-adrenergic receptors (720), acetylcholine (599), VIP and PACAP receptors (721), angiotensin II receptor-1 (722), adenosine A1 and A2B receptors (723) and the TSH receptor (724). Ligands of some of these receptors are known to modulate the function of immune cells.…”
Section: Paracrine Control By Nonhormonal Cellsmentioning
confidence: 99%